The Effectiveness of Sharia Economic Dispute Resolution in the Commercial Court related to Sharia Bankruptcy after the Constitutional Court Decision No. 93/PUU-X/2012 concerning Legal Certainty in the Settlement of Sharia Banking Cases - Harry Yuniardi; Muhamad Kholid; Laras Shesa (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
This research aims to identify the sources of material and formal law applied in the settlement of sharia economic disputes, evaluate the effectiveness of its implementation, and analyse the obstacles faced by religious courts at various levels. The data used includes cases in several religious courts and commercial courts in Indonesia in the period 2014-2020. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through document studies, interviews with religious court judges, and a review of relevant laws and regulations. Analyses were conducted to evaluate the application of material and formal law in dispute resolution, as well as to identify obstacles faced by religious courts in practice. The results of the study show that the material legal sources used in resolving sharia economic disputes include the Qur'an, Hadith, DSN-MUI fatwas, laws and regulations, and jurisprudence. Formal legal sources still depend on HIR/RBg as well as special regulations such as PERMA No. 14 of 2016. The religious court institutionally has shown readiness by increasing human resources, applying technology through e-courts, as well as efforts to provide technical guidance and certification of sharia economic judges. Religious courts have great potential to become the main institution in resolving sharia economic disputes. Improving regulations, codifying procedural law, and establishing sharia commercial courts in the future are needed to ensure legal certainty and efficiency of the dispute resolution process.